2016
DOI: 10.1111/his.12967
|View full text |Cite
|
Sign up to set email alerts
|

Fundic gland differentiation of oncocytic/pancreatobiliary subtypes of pancreatic intraductal papillary mucinous neoplasm

Abstract: The differentiation of IPMNs to gastric FG is related to oncocytic and pancreatobiliary subtypes, and to high grade. This is the first report to describe differentiation of IPMNs to the FG, and to reveal its relationship with the clinicopathological features of IPMNs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…7). We also conducted a somatic mutation analysis of G-protein αs (GNAS) and v-Ki-ras2 Kirsten rat sarcoma viral oncogene homolog (KRAS), as described previously (4). We analyzed The patient was followed for 10 months after resection; during this period, recurrence did not occur.…”
Section: Case Reportmentioning
confidence: 99%
“…7). We also conducted a somatic mutation analysis of G-protein αs (GNAS) and v-Ki-ras2 Kirsten rat sarcoma viral oncogene homolog (KRAS), as described previously (4). We analyzed The patient was followed for 10 months after resection; during this period, recurrence did not occur.…”
Section: Case Reportmentioning
confidence: 99%
“…Although they have some histological similarity to PGAs of the stomach, duodenum, and pancreas, the underlying molecular abnormalities are different; gallbladder PGAs frequently have the CTNNB1 mutation and exceptionally or only rarely have the KRAS mutation, and they lack the GNAS mutation. On the contrary, PGAs of the stomach, duodenum, and pancreas frequently have KRAS and GNAS mutations [ 24 , 25 , 26 , 27 ].…”
Section: Pyloric Gland Adenomamentioning
confidence: 99%
“…According to a recent study from our group, pancreatic PGAs did not show fundic gland differentiation; however the sample number was small. 16 In this study, no GB-PGA cases showed fundic gland differentiation, which was evaluated through pepsinogen I immunoreactivity.…”
mentioning
confidence: 91%
“…[10][11][12][13][14] In cases of pancreatic PGAs, or IPMN-PGs, high frequencies of GNAS/KRAS mutations have also been reported. 15,16 In contrast, only limited numbers of published studies are available on gallbladder PGAs (GB-PGAs), with respect to the histological variation, phenotypic differentiation, and, in particular, the molecular status of this neoplasm. Hence, to better understand GB-PGA, we aimed to investigate clinicopathological and immunohistochemical features as well as molecular status of this neoplasm by comparing with the reported data of those of stomach, duodenum and pancreatic PGAs (SDP-PGAs).…”
Section: Introductionmentioning
confidence: 99%